Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Berdasarkan Teori Newman (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study describes the common blunders made by pupils when solving mathematical problems by applying Newman's theory. A systematic literature review is employed in this study, which entails the following steps: (1) question formulation; (2) search strategy development; (3) data evaluation and analysis; and (4) interpretation and reporting of study findings. For this analysis, fifteen articles were considered. According to the findings, a lot of students need to work on their arithmetic problem-solving skills. According to Newman's approach, there are five common mistakes that students make: not understanding, not reading, not transforming, not using process skills correctly, and not writing the answers. When dealing with mathematical issues, such as story problems, this is a common occurrence. Errors are typically caused by students' lack of reasoning skills and originality when it comes to solving problems in real-world contexts and transforming them into algebraic form. First and foremost, it is critical that students develop a habit of appropriately using the problem-solving process